Editor's Note - Isa, Che Ruhana; Mohezar, Suhana (Asian Journal of Business and Accounting, 2018)
The Asian Journal of Business and Accounting (AJBA) is proud to present you with its 2018 first issue of volume 11. AJBA made its first debut in 2008 and during its course, the journal has strived to contribute to the academic discourse surrounding the business and accounting issues of Asia and the Pacific region. Throughout the years, AJBA has seen a steady increase in readership, article submissions and citations to our published articles. AJBA is indexed in the Emerging Sources Citation Index, Scopus, ERA, Asian Citation Index and MyCite. With a continuous and enhanced reputation that broadens visibility in the academic community, AJBA will soon succeed in its endeavour to be indexed in the Thomson Reuters Web of Science. In the current journal issue, we present a diverse selection of inspiring and interesting articles from both domestic and international scholars. The first article looks at how reputation, financial distress and financial performance influence Shariah-compliant companies into engaging earnings management behaviour. In this article, Ibrahim, Muhamad, Yusoff and Darus use the financial data of 69 FTSE Bursa Malaysia 100 Index companies, dating 2010 to 2014 (five years). Their study concludes that although Islamic values and principles may deter the management from carrying out unethical conducts, the failure of companies to adhere to holistic accounting practices and reporting may result in earnings management behaviour. In view of the increasing importance of Islamic values and principles, the second article by Graham and Sathye is a comparative study which examines how cross- cultural differences affect the capital budgeting system in Australia and Indonesia. They find empirical evidence to support the existence of sophisticated capital budgeting systems which are driven high level of perceived environmental uncertainty and Sharia governance rules in Indonesia. While an understanding of the dissimilarity between the national and foreign culture is crucial for managing businesses, it is also inevitable that each country will have its own institution which may generate institutional distances that can affect international operations. The distance may become larger in the context of a developed and a transition nation. The importance of this issue is addressed by Vo, Akhbar, Nguyen and Nguyen. They investigate the impact of institutional distance in the form of national culture and regulations between home and host countries and their choice of multinational enterprise’s (MNE) entry mode into Vietnam. Based on the Probit regression results, their study reveals that institutional distance between a host country and the home countries is an important element for MNEs to consider when making decisions to invest in a transition economy that contains high level uncertainties. In a contemporary global and competitive environment, the sustainability of a company not only depends on how it can effectively and efficiently pursue its investments in the international market by taking care of the national differences and values but also on how well it is managing the internal financial and operational affairs. In the fourth article, Nguyen and Mohanlingam present the findings of a study that investigates the relationship between cash conversion cycle and profitability that exists in the agriculture and food industries of Thailand. They analyse the data of 34 listed companies in the agriculture and food industry of the Stock Exchange of Thailand from 2009 to 2013. Using Pearson’s correlation and regression analysis, they find that cash conversion cycle (CCC) has a significant inverse relationship with profitability in the agriculture and food companies of Thailand. In the context of Indonesia, Hariyati and Tjahjadi examine how contextual variables which include innovation strategy, management accounting information systems and internal business process performance can affect the financial performance of manufacturing companies in the East Java Province of Indonesia. The results show that management accounting information systems and business process performance partially mediate the innovation strategy-financial performance relation- ship. This implies that managers need to improve the design and implementation of their accounting systems and their internal business process performance so as to support the firm’s innovation strategy which in turn, has an impact on the firm’s financial performance. In the subsequent article, Sofyani, Akhbar, and Ferrer look at the performance measurement system (PMS) implementation of the Indonesian local government by using a qualitative approach. The study highlights that whilst the PMS plays a significant role in improving performance and accountability, its implementation in Indonesia was underachieved due to the existence of institutional isomorphism at the coercive level. As more companies are expanding globally, Internet Financial Reporting (IFR) is becoming an increasingly important topic. Despite the importance of the IFR as a means of increasing the firm’s overall transparency, this practice is generally voluntary and unregulated, with many variations occurring in the manner companies implement their IFR practices. In the seventh article, Akmalia, Bin-Ghanem and Hashim examine the effect of ownership structure and Internet penetration of companies on their IFR practices. Their study aims to test whether Internet penetration moderates the relation between ownership and the IFR. Using data collected from companies in the Gulf Cooperation Council (GCC) countries, their study illustrates that companies with high government and family ownerships have lower extent of IFR. They also highlight that high quality IFR is evident in companies located in countries with a strong Internet penetration. For companies to serve the market better and to sustain their financial ability, it is pertinent that they obtain information about the current and future needs of their customers. When customers are satisfied with the values provided by the products or services offered, they are likely to repurchase and recommend the products to others. In light of this, Ansory and Safira use the questionnaire survey approach to predict the passengers’ behavioural intention of using railway services. The results show that different age groups have different evaluations and they used different determinants for gauging the railway services. This paper zooms in on Jakarta as it is one of the world’s largest agglomeration that is also acknowledged to have the worst traffic problems. Understanding the customers’ behavioural patterns of public transportation may facilitate in easing the escalating traffic congestion problem. In the following paper, Raut, Das and Kumar adopt the Theory of Planned Behaviour (TPB) to explain the individuals’ intention to invest in the capital market. Using data collected from 396 individuals in Eastern India through a survey, they find that attitude towards behaviour, subjective norms and perceived behavioural control is significantly associated with behavioural intentions. The findings also highlight that the inclusion of past behavioural biases can improve the predictive power of the model. With the tremendous growth of active Internet users and high Internet penetration rate, social media has grown to become a popular platform for electronic advertisements such that by word of mouth, the bloggers’ opinions and recommendations can affect the consumers’ purchase intention. In relation to this phenomenon of consumer behaviourism, the final paper in this issue examines the relationship between various antecedent factors affecting consumer attitude towards blogger recommendations and their purchase intention. Using data collected from 384 individuals in Sabah, Malaysia, the authors, Phang and Ming, highlight the relationships existing between consumer attitude and the antecedent factors namely, perceived usefulness, trustworthiness, information quality and perceived benefits. The study also confirms the mediation role of consumer attitude to- wards blogger recommendations. Most importantly, consumer attitude towards blogger recommendations is found to have a significant influence on consumer purchase intention. On a final note, we would like to thank the Malaysian Accountancy Research and Education Foundation as well as the Malaysian Ministry of Higher Education for the financial support extended. We also wish to say Thank You to the members of the editorial and advisory boards as well as the reviewers for their time and effort put into AJBA. We take this opportunity to show our appreciation and to thank AJBA’s former Co-chief Editor, Ainin Sulaiman and the Deputy Chief Editor, Chan Wai Meng, for their drive, dedication, passion and perseverance in managing the journal and also for bringing this journal to its current level. Thank you, and happy reading!